THE ARTICLE IS DEDICATED TO THE TEACHING METHODOLOGY OF USING THE SYSTEM OF THE MEANS OF THE FOLK ART IN FANNING ART CULTURE OF THE STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
The article is dedicated to the teaching methodology of using the system of the means o f the folk art in fanning art culture of the students. The ways of the intensification of the teaching and upbringing process of the readiness of the teachers-to be o f Handicraft during studying o f the disciplines o f Art are led to made conditional
Keywords: the system of the means of the folk art; art culture of the teacher